Installation of Solar Photovoltaic plants for educational purpose project - SIPHAXAY, Khamphoungeun (Souphanouvong University Journal Multidisciplinary Research and Development, 2016)
In this research would like to make Solar PV plant model for teaching students, Using energy from Solar PV plant to save power in University, Using solar system to make solar street light for security , in the research conclusion we get useful Solar system designing and have enough energy to charge 120Ah battery. The energy charging depends on the weather; if the weather has a lot of sunshine it can produce a lot of energy per day, solar panel has to charge 2.8 day to get battery full.Solar panel serial connection system is better than parallel connection system charging. One 150W solar panel charging all day In Luangprabang at 12 o’clock is the best time to get maximum energy 90.50W, all day the current hour is 41.62Ah and watts hour is 573.10Wh during sunny 90%.120Ah battery using with 60W LED lamp can use 7 night days.120Ah battery using time life by LED Solar Street light using with AC lamp and fan can use 16h.A payment of solar street light is less than streetlight system 3,281,280 kip for 30 year per one set. And we save energy 206.316 kWh per years for one set of solar street light or can save money 149,376 kip/year.